National Transfer Accounts Analysis for Sri Lanka - World Bank (Washington, DC, 2014)
Sri Lanka has been going through a demographic transition triggered by decreasing fertility and increasing life expectancy. The demographic transition is marked by two stages. During the first stage, the drop in new births reduces the under-age dependency ratio, while the proportion of working age population expands. This reduction in dependency ratio due to declining fertility, frequently referred to as the demographic bonus, is associated with an increased pace of economic development due to the larger share of working age population relative to the total population, and the smaller pool of dependents that workers have to support. In the second stage of the demographic transition, the consistently low fertility rates in combination with increased life expectancy for the elderly, lead to the relative expansion of the old-age dependency ratio. As the demographic transition enters the second stage, the demographic bonus deteriorates. As Sri Lanka is going through a demographic transition, it is important to take stock of the ways labor income is produced and consumed by different age groups. Similarly, when a deficit or a gap between consumption and labor income emerges, it is important to know what type of expenditures drive it and how it is financed. This paper documents labor income and consumption patterns by age group in Sri Lanka, in a manner that is comparable to work carried out for other countries that participate in the National Transfer Accounts Project.